A human pan-cancer system analysis of regulator of chromatin condensation 2. Issue 2 (February 2023) - Gong, Siming; Wu, Hao; Wu, Changwu; Duan, Yingjuan; Zhang, Bixi; Wu, Panfeng; Tang, Juyu; Fu, Jinfei
Abstract: Regulation of chromosome condensation 2 (RCC2) is associated with the cell cycle and is a crucial regulator of the chromatin condensation 1 (RCC1) family. The members of this family were normally regulators in the process of DNA replication and nucleocytoplasmic transport. RCC2 overexpression may lead to tumor formation and poor prognosis in some tumors including breast cancer and lung adenocarcinoma. However, the possible role of RCC2 in tumor formation and its prognostic function remains unclear. In this study, expression analysis from databases including The Cancer Genome Atlas (TCGA) and Clinical Proteomic Tumor Analysis Consortium (CPTAC) were combined to perform the first integrative and comprehensive analysis of RCC2 in human pan-cancer. RCC2 was highly expressed in most tumors which may lead to a poor prognosis. RCC2 expression was associated with immune/stromal infiltration, immune checkpoints, tumor mutational burden, and microsatellite instability. Thus, RCC2 could be a novel biomarker for prognosis and a promising cancer therapy target.